Characterization of rubberwood particleboard made using carboxymethyl starch mixed with polyvinyl alcohol as adhesive. (15th February 2020) - Lamaming, Junidah; Heng, Ng Boon; Owodunni, Amina Adedoja; Lamaming, Sofie Zarina; Khadir, Nurul Khizrien Abd; Hashim, Rokiah; Sulaiman, Othman; Mohamad Kassim, Mohamad Haafiz; Hussin, Mohd Hazwan; Bustami, Yazmin; Amini, Mohd Hazim Mohamad; Hiziroglu, Salim
Abstract: The aim of the study was to produce and characterize the modified starches and their suitability as wood adhesive for the particleboard manufacturing. The adhesive properties and particleboard manufactured from rubberwood using the modified starch and modified starch mixed with polyvinyl alcohol (PVA) were evaluated. Mixing of PVA with modified starch reduced the viscosity but increased the solid content and thermal property of the modified starch. Particleboard bonded with modified starch mixed with PVA also had improvement in physical and mechanical properties, showing great potential of modified starch and PVA as an adhesive for the green particleboard with good properties. Highlights: Commercial wheat starch was modified to carboxymethyl starch by carboxymethylation. Modified starch mixed with polyvinyl alcohol had better starch adhesive properties. Particleboard bonded with modified starch was more resistant to heat. Particleboard bonded with modified starch mixed with PVA showed better performance. Mechanical properties of modified starch mixed with PVA satisfied the standard used.